A beach vulnerability study at Copacabana beach, Rio de Janeiro: A study into the historic, present and future morphodynamic behavior of the beach focused on the impact of storm events and subsequent recovery - Hoogendoorn, Hugo (author) (2021)
Sandy beaches can be found all over the world and are on the interface between the sea and the land. Important functions of beaches are the protection of the inland to the forces of the sea and providing local opportunities in recreation. The impact of storm events on the beach is therefore an important topic of research especially with future climate change predicting more extreme events with the influence of Sea Level Rise expected to result in a worldwide decrease in beach area.The famous Copacabana beach, located at the South-Atlantic ocean is one of the most popular tourist attractions in Rio de Janeiro with thousands of visitors per year. The beach is characterized by its parabolic shape with rocky headlands on either sides. In July 2019 a storm event occurred at the beach with a 7-day period of energetic waves. This resulted in significant erosion along the whole beach up to 40 meters leaving not more than 10 meters of beach width in the South part of the beach. The period of erosion was followed up by a period with year-round average wave conditions resulting in rapid natural recovery with the beach returning to its original beach width within a period of 4 weeks. The focus of this research is on the cycle of erosion with subsequent recover which is important in having a long-term sustainable beach cycle.The history of Copacabana beach is marked by one major nourishment in 1970 which resulted in the 55 meter widening of the beach parallel avenue and an average widening of the beach of 35 meters. From 1970 onwards historically available satellite images show a stable beach behavior with the equilibrium profile of the beach showing smaller beach widths in the South compared to the North. A dataset of high resolution Sentinel 2 is analyzed in terms of beach width for a period of 4 years. This clearly shows the short-term variations in beach width of which most are the result of the impact of storm events. This highlights the impact of the July 2019 storm event showing rapid recovery in terms of beach ...